Poetry, Activism, and Queer Indigenous Imaginative Landscapes: Conversations with Janice Gould: Lisa Tatonetti - Tatonetti, Lisa (Transmotion, 2020)
This essay offers a final interview with Koyoonk’auwi writer and scholar Janice Gould (1949-2019). Tatonetti first contextulaizes Gould's work and then presents their discussion in three sections: Questions on Seed (2019), Gould's latest poetry collection; Questions on California; and Questions on Queer Indigenous History.